2015
DOI: 10.1186/s13028-015-0160-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the primary evaluation of 1016 horses with clinical signs of abdominal pain by veterinary practitioners, and the differentiation of critical and non-critical cases

Abstract: BackgroundThe majority of research on the evaluation of horses with colic is focused on referral hospital populations. Early identification of critical cases is important to optimise outcome and welfare. The aim of this prospective study was to survey the primary evaluation of horses with clinical signs of abdominal pain by veterinary practitioners, and compare the initial presentation of critical and non-critical cases.ResultsData from 1016 primary evaluations of horses presenting with clinical signs of colic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 37 publications
7
49
0
2
Order By: Relevance
“…The understanding of colic being a gastrointestinal malfunction is consistent with the study by Scantlebury et al . Although colic is primarily caused by gastrointestinal issues, it refers to abdominal pain, caused by diseases of any abdominal organs, and there may be a wide range of underlying causes . This misconception of a single disease may again relate back to issues around recognising different signs of colic.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The understanding of colic being a gastrointestinal malfunction is consistent with the study by Scantlebury et al . Although colic is primarily caused by gastrointestinal issues, it refers to abdominal pain, caused by diseases of any abdominal organs, and there may be a wide range of underlying causes . This misconception of a single disease may again relate back to issues around recognising different signs of colic.…”
Section: Discussionsupporting
confidence: 64%
“…A significant number also stated that if their horse had colic, they would assess some clinical parameters, specifically gut sounds (75%), respiration rate (65%) and heart rate (54%) before they contacted anyone else. These parameters can be important indicators of the severity of the condition . The findings of this study demonstrate owners’ willingness to be actively involved in the assessment of their horse’s health, but that there are issues with how their assessments may be interpreted.…”
Section: Discussionmentioning
confidence: 77%
“…Results of one study identified some referring veterinarians whose surgical colic cases had a higher risk of intra‐operative death than others , possibly because of delays in referral. More encouraging was the finding in a recent study that 96% of horses that had surgery for colic had one visit by a veterinarian at the farm , which would suggest that referring veterinarians can accurately identify those cases that should undergo surgery and could refer them promptly.…”
Section: Role Of Early Referral In Survivalmentioning
confidence: 99%
“…Colic episodes per 100 horse/equid years can range from 3.5 to 10.6 or as a percentage of equids at risk from 2.8 to 2.9% according to farm‐based studies or owner reported data. In the general equine population, approximately 1.4–17.5% of horses with colic require or undergo surgery . Improvements in surgical outcomes in horses with the most severe forms of colic have been attributed to early referral, advances in surgery, safer anaesthesia and improved aftercare .…”
Section: Introductionmentioning
confidence: 99%
“…A outra teoria, mais encontrada e citada, defende o estímulo vagal proporcionado pela acupuntura, o que aumenta a atividade parassimpática, consequentemente, estimulando a motilidade intestinal(FANG et al, 2017;OKADA et al, 2019). Este provavelmente foi o meio pelo qual se obteve aumento dos sons intestinais observados no presente estudo.Sabe-se que os sons intestinais indicam aumento da motilidade intestinal(BOSCAN et al, 2006;GERRING;HUNT, 1986;LIPPOLD;HILDEBRAND;STRAUB, 2004) e são considerados como um bom parâmetro para avaliação da condição da motilidade intestinal de equinos com cólica(CURTIS et al, 2015;JENNINGS et al, 2014). A auscultação intestinal é amplamente utilizada nas mais diversas vertentes da clínica equina e na pesquisa envolvendo equinos, desde avaliação da influência de dietas e fármacos na motilidade intestinal até a avaliação de dor(CARREGARO et al, 2014;DONNELLAN et al, 2013;GIUSTO;PAGLIARA;GANDINI, 2014;SALCICCIA et al, 2019;SANO et al, 2011;TAFFAREL et al, 2015).…”
unclassified